Best Poster by a First Timer - Veterinary Science and Open Access (Journal of EAHIL, 2017)
In our study we wanted to review the options available for preserving publications written by the teaching and research staff of the faculty taking into account copyright as well. We also compared article citations, and were surprised to learn that the articles receiving most citations were the ones self-archived, i.e. published in repositories, social networks, and author websites. Next we analysed students’ theses from the open access point of view, i.e. based on students’ copyright declarations. It is surprising to us that a generation brought up in a world of mobiles, tablets, laptops, and the internet does not take seriously the decision concerning their own theses and their online accessibility.